Efficacy of Parent–Child Interaction Therapy With Chinese ADHD Children: Randomized Controlled Trial. (January 2017) - Leung, Cynthia; Tsang, Sandra; Ng, Gene S. H.; Choi, S. Y.
Purpose: This study aimed to evaluate the efficacy of Parent-Child Interaction Therapy (PCIT) in Chinese children with attention-deficit/hyperactivity disorder (ADHD) or ADHD features. Methods: This study adopted a randomized controlled trial design without blinding. Participants were randomized into either the intervention group ( n = 32) and offered PCIT by trained PCIT practitioners or the waitlist control group ( n = 32) and offered PCIT after the intervention group had completed treatment. Parent participants were requested to complete questionnaires on their children's behavior and their parental stress. PCIT practitioners observed parent–child interactions according to a coding system. Results: Analysis was by intention to treat. The results indicated a significant decrease in child behavior and attention problems, parental stress, and negative parenting practices and an increase in positive parenting practices in the intervention group at postintervention ( p ≤ .002 in all cases). Conclusion: This study provided promising evidence on the effectiveness of PCIT in Chinese children with ADHD or ADHD features.